Key to tribes of family Paradoxosomatidae in Vietnam (Diplopoda: Polydesmida: Paradoxosomatidae) - Anh, Nguyen Duc (Academia Journal of Biology, 2014)
The paper presents the key to tribes of family Paradoxosomatidae (Diplopoda: Polydesmida) in Vietnam. Currently, 7 Paradoxosomatid tribes including Alogolykini, Nedyopodini, Tonkinosomatini, Sulciferini, Tectoporini, Sundaninini and Orthomorphini have been recorded in Vietnam. The paper also gives information of taxonomic diagnosis and distribution of these tribes in Vietnam. Key to tribes of family Paradoxosomatidae in Vietnam 1. - Gonofemorite strongly reduced. Solenomere separated from telopodite distinct at prefemorite (figs. 1-2)………………………………………………………………………………………....Alogolykini - Gonofemorite not reduced. Solenomere usually separated from telopodite at postfemorite…………….....2 2. - Both lamina medialis and lamina lateralis of gonopod tibiotarsus present or well-developed. Tibiotarsus not twisted (figs.4-12)………………………..……………………………………………………………....3 - Only lamina medialis of gonopod tibiotarsus present, while lamina lateralis strongly reduced. Solenomere is applied to or enclosed at the lateral side of the tibiotarsus. Tibiotarsus twisted (fig. 3)…………………………………...………………………………………………………..Tectoporini 3. - Gonopod telopodite relatively modestly expanded dorsally, devoid of a distinct suture setting off a post femoral portion. Seminal groove following a course along the lateral side of the femorite (figs. 4-5)…………...…………………………………………………………………………...Nedyopodini - Gonopod telopodite not expanded dorsally, with or without a distinct between femur and postfemur. Seminal groove only running a course along the mesal side of the femorite (figs. 6-12)…………………....4 4. - Gonopod femorite often broadened. Tibiotarsus well developed, strongly curved so as to form together with the femorite a circle or part of a circle (figs. 6-7)…………………………………….Tonkinosomatini - Gonopod femorite not broadened. Tibiotarsus not curved so as to form together with the femorite a circle or part of a circle (figs. 8-12)………………………………………………………………………………...5 5. - Femorite distally often with more than one distinct process and with a postfemoral part; tibiotarsus usually curved. Femorite often grooved on mesal side (figs. 8-9)…………………………………………Sulciferini - Femorite distally with or without a process, postfemoral part sometimes absent; tibiotarsus not curved. Femorite not grooved on mesal side…………………………………………………………………………6 6. - Solenomere fully mesal, attached to but not sheathed by a completely lateral tibiotarsus. Femorite with large spine (fig. 10)………………………………………………………………………………Sundaninini - Solenomere strongly to almost fully sheathed by tibiotarsus, the latter consisting of a lamina medialis and a lamina lateralis. Both lamina well developed. Femorite without spine (figs. 11-12)………Orthomorphini